Colonoscopic Removal of an Intrauterine Device That Had Perforated the Rectosigmoid Colon - Huh, Jin Myeong; Kim, Ki Seok; Cho, Yong Seok; Suh, Dong Kwon; Lee, Jae Uk; Baek, Seong Deuk; Moon, Sin Kil (Annals of coloproctology, 2018)
The intrauterine device (IUD) is a widely used contraceptive method. One of the most serious and rare complications of using an IUD is colon perforation. We report a case of colonoscopic removal of an IUD that had perforated into the rectosigmoid colon in a 42-year-old woman who presented with no symptoms. Colonoscopy showed that the IUD had penetrated into rectosigmoid colon wall and that an arm of the IUD was embedded in the colon wall. We were able to remove the IUD easily by using colonoscopy. The endoscopic approach may be considered the first choice therapy for selected patients.